2015
DOI: 10.1074/jbc.m114.631564
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Cytotoxic T Cell-derived Granzyme B Activates the Mitochondrial Cell Death Pathway in a Bim-dependent Fashion

Abstract: Background: Cytotoxic T cells employ perforin and granzyme B to kill tumor cells. Results: Bim-deficient 3T9-transformed MEF cells are resistant to gzmB-induced apoptosis. Conclusion:The mitochondrial apoptotic pathway activated via Bim is critically involved in apoptosis induced by mouse granzyme B. Significance: Learning how granzyme B induces apoptosis in different tumor cell types will help to predict and increase the efficacy of cancer immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…77 GzmB primarily induces apoptosis via the intrinsic mitochondrial pathway by either cleaving Bid or activating Bim leading to the activation of Bak/Bax and subsequent generation of active Casp-3. 78 CM of co-culture hWJMSCs and NK cells secreted GzmB which induced apoptosis (Table 4), induced Bax gene expression (Table 5), this results was consistent with previous research that the several proteins that are involved in gzmB-induced apoptosis, including casp-9 and -3, Bim, Bid, Bak, Bax, and XIAP and Bcl-2 was not detected. Gzm B induced apoptosis cancer cells by inlvolving induction of p53 tumor suppressor gene.…”
Section: Effect CM From Co-culture Of Hwjmscs and Ils-nk Towards Pro-supporting
confidence: 91%
“…77 GzmB primarily induces apoptosis via the intrinsic mitochondrial pathway by either cleaving Bid or activating Bim leading to the activation of Bak/Bax and subsequent generation of active Casp-3. 78 CM of co-culture hWJMSCs and NK cells secreted GzmB which induced apoptosis (Table 4), induced Bax gene expression (Table 5), this results was consistent with previous research that the several proteins that are involved in gzmB-induced apoptosis, including casp-9 and -3, Bim, Bid, Bak, Bax, and XIAP and Bcl-2 was not detected. Gzm B induced apoptosis cancer cells by inlvolving induction of p53 tumor suppressor gene.…”
Section: Effect CM From Co-culture Of Hwjmscs and Ils-nk Towards Pro-supporting
confidence: 91%
“…2). Notably, the mechanism of cell death activated by GZMB maybe dependent on the species (78) as well as on the type of cell transformation (96). In humans, it has been shown that cell cytotoxicity of cytokineactivated human NK cells is greatly reduced by inhibiting GZMB (97,98), confirming that GZMB is the main cell death inductor in CLs.…”
Section: Who Makes What During Cell Death Induced By Cls?mentioning
confidence: 74%
“…Indeed, GZMB has been shown to be crucial for CLmediated caspase-3 and Bid activation (93) and degradation of specific intracellular substrates such as tubulin (94,95), Mcl-1 (myeloid cell leukemia-1), or Bcl-x L (B-cell lymphoma-extra large; ref. 96). Importantly, these events occurred before membrane permeabilization could be detected (Fig.…”
Section: Who Makes What During Cell Death Induced By Cls?mentioning
confidence: 99%
“…Additionally, NK-cells' granules can also contain granzyme-M [56]. While granzyme-B can directly activate effector caspases-3 and -7, it preferentially mediates target cell killing by activating the intrinsic pathway of apoptosis through the cleavage of BIM and/or BID [57][58][59].…”
Section: Apoptosis the Main Mechanism Of Immune Cell-mediated Tumor mentioning
confidence: 99%